2016
DOI: 10.3389/fnmol.2016.00019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Regulating LPS-Induced Inflammation in the Brain

Abstract: Neuro-inflammation, one of the pathogenic causes of neurodegenerative diseases, is regulated through the cholinergic anti-inflammatory pathway via the α7 nicotinic acetylcholine receptor (α7 nAChR). We previously showed that either bacterial lipopolysaccharide (LPS) or immunization with the α7(1–208) nAChR fragment decrease α7 nAChRs density in the mouse brain, exacerbating chronic inflammation, beta-amyloid accumulation and episodic memory decline, which mimic the early stages of Alzheimer’s disease (AD). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 61 publications
3
44
0
Order By: Relevance
“…A single injection of LPS intraperitonially caused neuroinflammation in rats via the TLR-4 signaling pathway, which further activates various intracellular molecules that affect the expression of a plethora of steady-state transcripts such as TNF-α, NO, and PGE 2 in the serum and brain homogenates [59,61]. In addition, the up-regulated of AChE activity upon the LPS injection in the present study was found in consonance with preceding reports [62][63][64]. This observation might reflect the deficit of cholinergic neurotransmission in the brain and further supports the impression that altered activity of AChE that has been found in patients with AD is attributed by the overexpression of pro-and anti-inflammatory cytokines [65].…”
Section: Discussionsupporting
confidence: 92%
“…A single injection of LPS intraperitonially caused neuroinflammation in rats via the TLR-4 signaling pathway, which further activates various intracellular molecules that affect the expression of a plethora of steady-state transcripts such as TNF-α, NO, and PGE 2 in the serum and brain homogenates [59,61]. In addition, the up-regulated of AChE activity upon the LPS injection in the present study was found in consonance with preceding reports [62][63][64]. This observation might reflect the deficit of cholinergic neurotransmission in the brain and further supports the impression that altered activity of AChE that has been found in patients with AD is attributed by the overexpression of pro-and anti-inflammatory cytokines [65].…”
Section: Discussionsupporting
confidence: 92%
“…While other recent studies have reported an LPS-mediated stimulation of chronic inflammation, beta-amyloid accumulation, and episodic memory decline in murine models of AD ( 39 , 40 ) and a biophysical association of LPS with amyloid deposits and blood vessels in human AD patients ( 18 ), here, we provide the first evidence of a perinuclear association of LPS with AD brain cell nuclei (Figures 1 E,F). Strong adherence of LPS to the nuclear periphery has recently been shown to inhibit nuclear maturation and function that may impair or block export of mRNA signals from brain cell nuclei, a highly active organelle with extremely high rates of transcription, mRNA processing, and export into the cytoplasm [( 41 43 ), unpublished observations].…”
Section: Perinuclear Localization Of Lps In Ad Brainssupporting
confidence: 54%
“…This may in part be responsible for the widely observed, generalized downregulation of global gene expression in AD, independently reported by several AD gene expression research laboratories, through the biophysical blockage of mRNA trafficking through nuclear pores ( 41 , 42 , 44 , 45 ). LPS may be further injurious to the nuclear membrane just as LPS contributes to cerebrovascular endothelial cell membrane injury ( 12 , 18 , 40 ). Lastly, evidence is accumulating that neurotoxic exudates from other GI-tract microbiota may contribute to dysfunction in additional, ultimately fatal neuropsychiatric illnesses that involve progressive inflammatory neurodegeneration ( 8 , 12 ).…”
Section: Perinuclear Localization Of Lps In Ad Brainsmentioning
confidence: 99%
“…The role of microglia-mediated neuroinflammation in the progressive nature of many neurodegenerative disorders has been demonstrated in models of microglial cells activated by pro-inflammatory stimuli [2]. Lipopolysaccharide (LPS), an endotoxin expressed in the external membrane of Gram-negative bacteria, has been widely employed to provoke the neuroinflammatory processes through the secretion of various cytokines and eicosanoids [2,13]. It has been reported that LPS-activated microglia can initiate neuronal cell damage [14,15], resulting in delayed and progressive degeneration of neurons over time [14,16].…”
Section: Introductionmentioning
confidence: 99%